Formation institution private farms as a component of agricultural land use - Kupriyanchyk, I. P. (Land Management, Cadastre and Land Monitoring, 2017)
Investigated the features of the functioning and development of private farms in market conditions, reveals inconsistency of legal norms of these farms. Proved that the introduction of personal peasant economy will help improve the legal norms of these farms to improve financial and credit policy of the state of their development and promote the competitiveness of small and medium agricultural enterprises.